PsycEXTRA Dataset 2005
DOI: 10.1037/e645102011-001
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Administering Large-Scale Content Assessments to English Language Learners: An Investigation From Three Perspectives

Abstract: Data from a large public school district (referred to as Site 1 from this point on) for Grades 2 through 8 for the 1999 student population were analyzed for all students including English language learners (ELLs). The data included student responses to the reading and mathematics subtests of the Iowa Tests of Basic Skills 2 (ITBS) and student background data such as race, gender, birth date, and number of years of participation in a bilingual education program (number of years of bilingual service). Descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 14 publications
2
30
2
Order By: Relevance
“…Although these effects may not be consistent across all items, in aggregate on an assessment, the effects of LC and accommodations may form a different test for students with diverse language backgrounds. Abedi et al (2005) found a difference in the internal consistency of test scores for ELL students versus non-ELL students; LC and accommodations may lead to similar results for SLD. Although the reasons for challenges with high LC are different for both ELL students and SLD, high LC may be a potential obstacle to optimal performance on assessment items (and particularly, reading items) for both groups.…”
Section: Linguistic Complexitysupporting
confidence: 56%
See 1 more Smart Citation
“…Although these effects may not be consistent across all items, in aggregate on an assessment, the effects of LC and accommodations may form a different test for students with diverse language backgrounds. Abedi et al (2005) found a difference in the internal consistency of test scores for ELL students versus non-ELL students; LC and accommodations may lead to similar results for SLD. Although the reasons for challenges with high LC are different for both ELL students and SLD, high LC may be a potential obstacle to optimal performance on assessment items (and particularly, reading items) for both groups.…”
Section: Linguistic Complexitysupporting
confidence: 56%
“…Research has shown that unnecessarily complex language (e.g., uncommon vocabulary, words with multiple meanings, or complicated word clauses) may interfere with a student's ability to exhibit content knowledge on a standardized assessment and that this interference can hinge on student English language proficiency (e.g., Abedi, Hofstetter, & Lord, 2004;Abedi & Lord, 2001;Abedi et al, 2005). For example, it has been shown that ELL students have a more difficult time than their non-ELL student peers accurately answering questions with a high discourse demand, or language processing beyond the sentence level (Abedi et al, 2005). In addition to the effects of accommodations, the concept of language demand of assessment items is an important consideration when interpreting the scores of students with potential language processing challenges.…”
Section: Linguistic Complexitymentioning
confidence: 99%
“…For example, items with ambiguous or multiple meaning words were more difficult than items with fewer or none of these features for both ELLs and non-ELLs in the fourth-grade KGMA, but this effect was not significant in the seventh and tenth grades (Shaftel et al, 2006). Likewise, the presence of idioms, uncommon words and/or words used in an uncommon way was not significantly correlated with (unconditional) item p value differences across ELLs and non-ELLs in a third-grade math subtest of a standardized achievement test (Abedi et al, 2005). Neither was the presence of low-frequency vocabulary in the third and eighth grade SAT9 (Lord et al, 2000).…”
Section: Previous Research On Linguistic Complexity and Math Performamentioning
confidence: 80%
“…The presence of complex or uncommon syntactic structures did not show significant correlations with group p value differences in the third-grade math subtest, whereas the presence of multiple clauses did (r D .32, p D .02; Abedi et al, 2005). Neither the number of passive voice sentences nor the number of subordinate clauses has shown significant effect in any of the tests and grades studied (NAEP Grade 8 in Abedi et al, 1997; SAT9 Grades 3 and 8 in Lord et al, 2000;KGMA Grades 4, 7, and 10 in Shaftel et al, 2006).…”
Section: Previous Research On Linguistic Complexity and Math Performamentioning
confidence: 87%
See 1 more Smart Citation